Amyloidogenic mutations in human apolipoprotein A‐I are not necessarily destabilizing – a common mechanism of apolipoprotein A‐I misfolding in familial amyloidosis and atherosclerosis. (28th April 2014) - Das, Madhurima; Mei, Xiaohu; Jayaraman, Shobini; Atkinson, David; Gursky, Olga
<x xml:space="preserve">Abstract</x> High‐density lipoproteins and their major protein, apolipoprotein A‐I (apoA‐I), remove excess cellular cholesterol and protect against atherosclerosis. However, in acquired amyloidosis, nonvariant full‐length apoA‐I deposits as fibrils in atherosclerotic plaques; in familial amyloidosis, N‐terminal fragments of variant apoA‐I deposit in vital organs, damaging them. Recently, we used the crystal structure of Δ(185–243)apoA‐I to show that amyloidogenic mutations destabilize apoA‐I and increase solvent exposure of the extended strand 44–55 that initiates β‐aggregation. In the present study, we test this hypothesis by exploring naturally occurring human amyloidogenic mutations, W50R and G26R, within or close to this strand. The mutations caused small changes in the protein's α‐helical content, stability, proteolytic pattern and protein–lipid interactions. These changes alone were unlikely to account for amyloidosis, suggesting the importance of other factors. Sequence analysis predicted several amyloid‐prone segments that can initiate apoA‐I misfolding. Aggregation studies using N‐terminal fragments verified this prediction experimentally. Three predicted N‐terminal amyloid‐prone segments, mapped on the crystal structure, formed an α‐helical cluster. Structural analysis indicates that amyloidogenic mutations or Met86 oxidation perturb native packing in this cluster. Taken together, the results suggest that structural perturbations in the amyloid‐prone segments trigger α‐helix to β‐sheet conversion in the N‐terminal ~ 75 residues forming the amyloid core. Polypeptide outside this core can be proteolysed to form 9–11 kDa N‐terminal fragments found in familial amyloidosis. Our results imply that apoA‐I misfolding in familial and acquired amyloidosis follows a similar mechanism that does not require significant structural destabilization or proteolysis. This novel mechanism suggests potential therapeutic interventions for apoA‐I amyloidosis. Structured digital abstract apoA-I and apoA-I bind by fluorescence technology (View interaction) apoA-I and apoA-I bind by electron microscopy (View interaction)